Strategic issues on growth in the agricultural sector and reducing poverty in Nigeria - Diao, Xinshen; Nwafor, Manson; Alpuerto, Vida (International Food Policy Research Institute, 2010)
Designing agricultural strategies requires an understanding of the options for dealing with growth in the sector, its impact on targeted beneficiaries, and the investment required to achieve the growth. IFPRI's recent study identified agricultural growth and development options that can support comprehensive rural development in Nigeria, in line with its national agricultural strategy - the National Food Security Program - over the next nine years (2009-2017). This research highlighted five key issues to be considered when developing and updating agriculture strategies that aim to alleviate poverty through accelerated growth in the agriculture sector.